The Effect of Composite Composition Ratio on the Physicochemical Characteristics of Bovine Hydroxyapatite-Chitosan-Ciprofloxacin Implant: Effect of Composite Composition on BHA-Chit-Cipro Implant - Karina Citra Rani; Teguh Imanto; Riesta Primaharinastiti; Dewi Melani Hariyadi; Esti Hendradi (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2019)
This study aimed to develop bone implant as either deliver ciprofloxacin to the bone or regenerate bone defects. The effect of the composite composition ratio (Bovine Hydroxyapatite-Chitosan) on the physicochemical characteristics of Bovine Hydroxyapatite Chitosan-ciprofloxacin implant were evaluated in this study. Ciprofloxacin implants were prepared using four different compositions of composite (Bovine Hydroxyapatite-Chitosan) 20:80; 30:70; 40:60; and 70:30. The amount of ciprofloxacin in each implant was 10 %. The powder mixture was then pressed into pellets. The implants were evaluated by various parameters such as porosity, density, water absorption capacity, swelling ratio, disintegration test, compression force, drug assay, and in vitro drug release. Characterization of the implants was conducted using Fourier Transform Infrared (FT-IR), Scanning Electron Microscopy (SEM), and X-ray diffraction study. The results obtained from this work revealed that the composite composition ratio (Bovine Hydroxyapatite-Chitosan) influenced the differences in physical characteristics and the release of ciprofloxacin from Bovine Hydroxyapatite-Chitosan-ciprofloxacin implant. The increased in the Bovine Hydroxyapatite ratio in composite composition caused enhancement of physical characteristics (porosity, density, water absorption capacity, and compressive strength) of the implant. Meanwhile, increase in Bovine Hydroxyapatite ratio in implant caused lower release of ciprofloxacin. The best composite composition ratio to produce Bovine Hydroxyapatite-Chitosan-ciprofloxacin implant with desired physical characteristics and ciprofloxacin release was Bovine Hydroxyapatite-Chitosan (70:30).